Association between sporting event attendance and self-rated health: an analysis of multiyear cross-sectional national data in Japan - Yuhei Inoue; Mikihiro Sato; Makoto Nakazawa (BMC, 2018)
Abstract Background This study examined the extent to which sporting event attendance is associated with self-rated health. Drawing from an economic model of health production and psychological research on the health benefits of psychosocial resources, sporting event attendance was hypothesized to have a positive relationship with self-rated health. Methods A two-level multilevel ordered logistic regression was used to analyze multiyear cross-sectional data collected from national surveys in Japan. Results The results demonstrate that, controlling for the effects of personal and environmental characteristics, sporting event attendance positively correlates with self-rated health over a 12-year period. Specifically, when compared to individuals who did not attend any sporting event during the past year, those who attended a sporting event were 33% more likely to indicate a higher level of self-rated health. Conclusions These findings provide evidence for a positive association between sport spectatorship and the perception of general health and contribute to the literature examining the relationship between sport spectatorship and health outcomes.